Intercalative hybridization of layered double hydroxide nanocrystals with mesoporous g-C3N4 for enhancing visible light-induced H2 production efficiency. Issue 9 (24th November 2017) - Lee, Jang Mee; Yang, Jae-Hun; Kwon, Nam Hee; Jo, Yun Kyung; Choy, Jin-Ho; Hwang, Seong-Ju
Abstract : Highly efficient visible-light-active hybrid photocatalysts with enhanced electronic coupling are synthesized via the intercalative hybridization of Zn–Cr-LDH nanocrystals with mesoporous g-C3 N4 . Abstract : Efficient visible light active hybrid photocatalysts for H2 production can be synthesized by the intercalative hybridization of Zn–Cr-layered double hydroxide (Zn–Cr-LDH) with a mesoporous g-C3 N4 lattice. Small Zn–Cr-LDH nanocrystals with a size of ∼6 nm are immobilized in the mesopores of g-C3 N4 . Beyond an optimal LDH/g-C3 N4 molar ratio of 0.3, a further increase in the LDH content leads to the surface deposition of LDH crystals on the g-C3 N4 material as well as the intercalative immobilization of LDH into its mesopores, indicating the controllability of the LDH deposition site. The Zn–Cr-LDH−g-C3 N4 nanohybrids exhibit smaller surface areas than the pristine g-C3 N4, confirming the intercalative stabilization of Zn–Cr-LDH nanocrystals in the mesopore of g-C3 N4 . The hybridization between Zn–Cr-LDH and g-C3 N4 is effective in enhancing visible light absorptivity and also in depressing electron−hole recombination, which is attributable to an efficient electronic coupling between both the hybridized components. The present Zn–Cr-LDH−g-C3 N4 nanohybrid exhibits promising photocatalytic activities for visible light-induced H2 production at a rate of 155.7 μmol g −1 h −1, which is much superior to that of the pristine g-C3 N4 (21.7 μmol g −1 h −1 ). The present study underscores that the intercalative immobilization of Zn–Cr-LDH crystals in the limited space of a mesopore is quite useful in improving the visible light active photocatalyst functionality of mesoporous carbon nitride.